Use of in vivo-regulated promoters to deliver antigens from attenuated Salmonella enterica var. typhimurium - Simmons, Cameron (2018)
This study describes the construction and analysis of three in vivo-inducible promoter expression plasmids, containing pnirB, ppagC, and pkatG, for the delivery of foreign antigens in the DeltaaroAD mutant of Salmonella enterica var. Typhimurium (hereafter referred to as S. typhimurium). The reporter genes encoding beta-galactosidase and firefly luciferase were used to assess the comparative levels of promoter activity in S. typhimurium in vitro in response to different induction stimuli and in vivo in immunized mice. It was determined that the ppagC construct directed the expression of more beta-galactosidase and luciferase in S. typhimurium than the pnirB and pkatG constructs, both in vitro and in vivo. The gene encoding the C fragment of tetanus toxin was expressed in the aroAD mutant of S. typhimurium (BRD509) under the control of the three promoters. Mice orally immunized with attenuated S. typhimurium expressing C fragment under control of the pagC promoter [BRD509(pKK/ppagC/C frag)] mounted the highest tetanus toxoid-specific serum antibody response. Levels of luciferase expression in vivo and C-fragment expression in vitro from the pagC promoter appeared to be equivalent to if not lower than the levels of expression detected with the constitutive trc promoter. However, mice immunized with BRD509(pKK/ppagC/C frag) induced significantly higher levels of tetanus toxoid-specific antibody than BRD509(pKK/C frag)-immunized mice, suggesting that the specific location of foreign antigen expression may be important for immunogenicity. Mutagenesis of the ribosome binding sites (RBS) in the three promoter/C fragment expression plasmids was also performed. Despite optimization of the RBS in the three different promoter elements, the expression levels in vivo and overall immunogenicity of C fragment when delivered to mice by attenuated S. typhimurium were not affected. These studies suggest that in vivo-inducible promoters may give rise to enhanced immunogenicity and increase the efficacy of S. typhimurium as a vaccine vector.